LOOKing for Multi-word Expressions in American Sign Language - Hou, Lynn (Dryad, 2020)
Usage-based linguistics postulates that multi-word expressions constitute
a substantial part of language structure and use, and are formed through
repeated chunking and stored as exemplar wholes. They are also re-used to
produce new sequences by means of schematization. While there is extensive
research on multi-word expressions in many spoken languages, little is
known about the status of multi-word expressions in the mainstream U.S.
variety of American Sign Language (ASL). This paper investigates recurring
multi-word expressions, or sequences of multiple signs, that involve a
high-frequency sign of visual perception glossed as LOOK and the family of
‘look’ signs. The LOOK sign exhibits two broad functions: LOOK/‘vision’
references literal or metaphorical vision and LOOK/‘reaction’ signals a
person’s reaction to a visual stimulus. Data analysis reveals that there
are recurring sequences in distinct syntactic environments associated with
the two functions of LOOK, suggesting that LOOK is in the process of
grammaticalization from a verb of visual perception to a stance verb. The
sequences demonstrate the emergence of linguistic structure from repeated
use through the domain-general cognitive process of chunking in ASL.
This dataset was collected by an arbitrary sampling of assorted videos and
video blogs (vlogs) in American Sign Language from the internet. These
videos were coded for all tokens of the family of 'look' and
'see' signs and the five signs preceding the target sign and the
five signs following it. The target sign was also analyzed for their
function in the phrasal context. The coding was entered as English glosses
in a Microsoft Excel spreadsheet. Then the data was sorted for their
functions and also sorted for recurring n-grams.
The majority of the videos are available on YouTube and Vimeo. A few are
available through Facebook, which requires an account for logging in to
view public posts on individual pages but not in public groups. Other
videos are no longer available for public viewing or missing, and thus
there are no links provided for these videos.
Keywords: FOS: Languages and literature; American Sign Language; multi-word expressions; chunking; grammaticalization; visual perception